Toxicity test of jatropha leaf filtrate (Jatropha curcas L.) on mortality of golden snail (Pomacea canaliculata) - Maruni, Mulyadi; Lamangantjo, Chairunnisah J.; Abdul, Aryati (Univeritas Papua, 2022)
This study was an experimental study to determine the effect of the toxicity of Jatropha curcas L. leaf filtrate on the mortality of the Pomacea canaliculata (golden snail). Pomacea canaliculata as many as 240 tails aged 7 days after hatching is the object of research. A completely randomized design of 6 (treatment) and 4 (replication) was used in this study. Data was collected by observing the golden snail every hour for 24 hours. ANAVA and BNT analysis to calculate research data. Calculation of 50% mortality of research objects using LC50. The ANAVA results are Fcount 434.160 > Ftable 2.64. The findings indicated that the filtrate from Jatropha curcas leaves had toxicity on golden snail mortality. The concentration of jatropha leaf filtrate that can kill the golden snail is 7% based on calculations with LC50. This concentration was able to kill half of the golden snails tested.